(untitled) (Filološke pripombe, 2019)
Proceeding from Aristotle’s Poetics and some other sources (Lexicon Suidas), the author traces the beginnings of Greek pre-tragic tragedy. With the analysis of the dithyramb and satiric play he establishes its origin in the ritual, thus in the unity of dance, music and verbal elements, where the only possible turn of events in this short, humorous play was from misfortune to good fortune.